Does Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) reflect the impact of malocclusion on facial aesthetics? - Mohammed FARAJ; Sundareswaran SHOBHA; Vadakkeypeediakkal LATHEEF; Prakash NIVEDITA (Dental Press Editora, 2023)
ABSTRACT Introduction: Malocclusion is presumed to have adverse effects on dental and facial attractiveness, leading to deleterious psychosocial impact and Quality of life(QoL) of the individual. The Psychosocial Impact of Dental Aesthetic Questionnaire (PIDAQ) has proved to be effective for assessment of psychosocial impact of malocclusion on dental aesthetics, but it's effectiveness for assessing facial aesthetics is unknown. Objective: The aim of the present study was to assess the effectiveness of PIDAQ on its ability to reflect the psychosocial impact of malocclusion on facial attractiveness, using the Facial Aesthetic index (FAI) after its translation and validation in the regional language. Methods: The 23-item PIDAQ, after translation process, cross-cultural adaptation and pilot testing, was administered to 330 subjects (62.5 % females and 37.5 % males; age range 18-30 years) with varying degrees of severity of malocclusion, assessed by the two components of the Index of Orthodontic Treatment Need (Dental Health Component, IOTN-DHC, for normative need; and self-administered Aesthetic Component, IOTN-AC, for subjective need) and FAI. Results: The internal consistency and test-retest reliability were good (Cronbach's alpha = 0.859 - 0.958; Intraclass correlation coefficient =0.984). FAI, IOTN-DHC and IOTN-AC scores showed highly significant correlation with PIDAQ scores, depicting strong convergent validity (p< 0.001). One-way analysis of variance (ANOVA) and Bonferroni post-hoc test showed highly significant correlations (p-value < 0.001) for all comparisons. There were no significant differences between responses of males and females. The regional version of PIDAQ had excellent reliability. Conclusions: PIDAQ showed good psychometric properties and was able to effectively reflect the psychosocial impact of malocclusion on altered facial aesthetics.